Perancangan Jaringan Fiber Optik Di Kantor Bahasa NTB Menggunakan Topology FTTH Dengan Teknologi GPON - Sadri, Muhammad; Tantoni, Ahmad; Fadli, Sofiansyah (Universitas Gajah Putih, 2023)
Every year, the Demand for the Demand for services like internet, telephone, and TV broadcasting continues to increase over time. Advances in thisItype of service are known as tripleIplay.IFTTHIis a fiber-optic-based communicationsInetwork infrastructure that enables the provision of triple play services directly to home users. This study aims to design device configurations and network architectures that utilize GPON technology in an FTTH distribution network that uses GPON technology in the language office of PT. Net Fiber. This study uses an experimental method to measure network feasibility standard parameters to design a network design in the Language office using FTTH topology with GPON technology. Furthermore, in this study, manual calculationsIwere carried outIto evaluate the feasibility of the network to be built based on predetermined standards. Based on the manual calculation of network eligibility standards, it was found that the farthest attenuation value in the Power Budget link reached 24.49 dB,Iwhile the highest value in the RiseITime Budget was 0.2762 ns. The resultsIof theseIcalculations are in accordance withIthe eligibilityIstandards set byIPT. FiberNet for distribution network.